2007
DOI: 10.1111/j.1740-8261.2007.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sedation With Midazolam and Butorphanol on Resistive and Pulsatility Indices in Healthy Dogs

Abstract: Resistive index (RI) and pulsatility index (PI) are indirect measurements of blood flow resistance that may be measured by pulsed wave Doppler ultrasonography. Chemical restrain may potentially alter the indices although it is required to perform ultrasonography in some patients. The purpose of this study was to describe values for both intrarenal and ocular RI and PI within the same subject in clinically normal dogs sedated with a midazolam and butorphanol combination and evaluate if there are any significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
2
22
1
6
Order By: Relevance
“…Lee et al (2002), Sindak et al (2003) and Novellas et al (2007b) reported that there were no significant differences in the RI values between the left and right eyes, or between male and female dogs of different breeds. The results of this present study support the findings of these authors, because we similarly did not find any significant differences in RI between left and right eyes or between male and female cats.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lee et al (2002), Sindak et al (2003) and Novellas et al (2007b) reported that there were no significant differences in the RI values between the left and right eyes, or between male and female dogs of different breeds. The results of this present study support the findings of these authors, because we similarly did not find any significant differences in RI between left and right eyes or between male and female cats.…”
Section: Discussionmentioning
confidence: 96%
“…The effects of certain sedative protocols on Doppler variables of different canine ocular arteries has already been character- Novellas et al 2007b). Intramuscular administration of midazolam and butorphanol increases ocular blood flow resistance (Novellas et al 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, a similar decrease in BP has been observed during the first 20 min post-injection of a butorphanol-midazolam combination (Kojima et al, 1999), with intramuscular doses of 0.2 mg/kg each decreasing SAP by 15 mmHg (Novellas et al, 2007). Since we could not measure NIBP in unsedated ferrets, it was not possible to determine whether midazolam and butorphanol affected BP at the dosages used in our study.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies (Greenblatt et al, 1992;Kanaya et al, 1998) have suggested that isoflurane modifies responses to endotheliumdependent vasodilators and peripheral vascular resistance, which leads to the decrease of artery blood pressure. Experiments (Wiktorowska et al, 1999;Novellas et al, 2007) have shown that iv midazolam caused a gradual fall of artery blood pressure. In Ahmad et al (2000)'s study, two groups of piglets (1-3 d old, 1.0-1.5 kg) received either (1) a loading dose of 300 μg/kg of midazolam over 15 min, followed by a continuous intravenous infusion of 100 μg/(kg·h) (n=6), or (2) equivalent volume bolus and intravenous infusions of 0.05 g/ml dextrose (control, n=8).…”
Section: Discussionmentioning
confidence: 99%